Evaluation of Healthy Canine Conjunctival, Periocular Haired Skin, and Nasal Microbiota Compared to Conjunctival Culture - Banks, Kayla C.; Giuliano, Elizabeth A.; Busi, Susheel B.; Reinero, Carol R.; Ericsson, Aaron C. (Frontiers in Veterinary Science, 2020)
Next generation sequencing (NGS) methods have been used to identify a diverse ocular surface (OS) microbiota in humans. These results have highlighted limitations in microbial detection via traditional culture-based techniques. The OS has mechanisms such as tear film and mechanical blinking which may aid in preventing adherence and colonization of microbes, suggesting only low populations of microbes may reside on the OS. Additionally, closely related tissues to the OS are exposed to a similar array of microbes, but demonstrate different defense mechanisms. Information regarding concordance of microbial communities of the OS and nearby tissues is lacking. Our study purposes were to (1) characterize the conjunctival microbiota of healthy dogs, (2) compare the conjunctival microbiota to the periocular haired skin and distal nose, and (3) compare the bacteria identified by culture to NGS of the healthy canine conjunctiva. Here, 25 healthy adult dogs were sampled using NGS of the conjunctiva, periocular haired skin, and distal nose. Additional samples were collected from each dog for traditional conjunctival culture. The 16S rRNA gene amplicon libraries were evaluated for coverage, relative abundance, richness, and diversity. Site-dependent similarities evaluated using principal coordinates analysis (PCoA) and PERMANOVA demonstrated relatedness in community compositions between sites. The conjunctiva of healthy dogs yielded a rich and diverse microbiota based on NGS. While some regional continuity was noted, microbial communities of the conjunctiva, periocular haired skin, and nose were significantly different from each other. Nasal and conjunctival microbial communities were more closely related when evaluated by richness and unweighted β‐diversity. Comparatively, traditional culture markedly underestimated the number of bacterial taxa present on the healthy canine OS. Findings suggest greater similarities in nasal and conjunctival microbial communities which may be a result of similarities in mucosal immunity and anatomic connection via the nasolacrimal system. Further investigation using NGS into changes of the composition of bacterial communities in disease is warranted.